Navigating Global Realities: An In-Depth Analysis of The Legal and Institutional Framework of Nigerian Foreign Policy - Okpevra, Uwomano Benjamin; Usiemure, Christopher Oghenerioborue (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2024)
This article provides a critical examination of the complex legal and institutional framework that shapes Nigerian foreign policy, highlighting its evolution, challenges, and implications within the contemporary global context. Positioned as a key player in African affairs, Nigeria's foreign policy is guided by a set of legal foundations and institutional mechanisms that have developed since the country's post-independence era. Through a historical lens, this study traces the key milestones, shifts, and guiding principles that have influenced Nigeria's foreign policy trajectory. The paper offers a comprehensive analysis of relevant laws, treaties, constitutional provisions, and the roles of key governmental bodies and diplomatic institutions. By exploring the interplay between these legal frameworks and institutional structures, this research provides valuable insights into the dynamics that shape Nigeria's interactions on the global stage, contributing to a deeper understanding of the country's role in international relations.